2018
DOI: 10.1002/npr2.12002
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of long‐term oral administration of aluminum ammonium sulfate in male and female C57BL/6J mice

Abstract: Background: Aluminum (Al) is considered to be a neurotoxic metal, and excessive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Most literature data about the low dose Al toxicity is based on the experiments where Al is administered orally. Direct evidence of neurotoxicity due to low doses of Al is controversial, e.g., Shoji et al reported that 0.97-9.7 mg/kg/day Al per os for 60 days did not induce statistically significant behavioral changes in C57BL/6J mice [35], whereas Martinez et al found that 8.3 mg/kg/day Al per os for 60 days promoted the development of mechanical allodynia, catalepsy, increased inflammation in the sciatic nerve, and systemic oxidative stress, and was able to be retained in the sciatic nerve [36].…”
Section: Discussionmentioning
confidence: 99%
“…Most literature data about the low dose Al toxicity is based on the experiments where Al is administered orally. Direct evidence of neurotoxicity due to low doses of Al is controversial, e.g., Shoji et al reported that 0.97-9.7 mg/kg/day Al per os for 60 days did not induce statistically significant behavioral changes in C57BL/6J mice [35], whereas Martinez et al found that 8.3 mg/kg/day Al per os for 60 days promoted the development of mechanical allodynia, catalepsy, increased inflammation in the sciatic nerve, and systemic oxidative stress, and was able to be retained in the sciatic nerve [36].…”
Section: Discussionmentioning
confidence: 99%
“…At least 30 minutes before the beginning of each test, the mice were transferred to sound‐attenuated rooms adjacent to the housing room and acclimated to the room set up for each test (see Refs ). The mice were tested in the following order: general health and neurological screen, light/dark transition, open field, elevated plus maze, hot plate, social interaction, rotarod, three‐chamber social approach, ASR/PPI, Porsolt forced swim, T‐maze spontaneous alternation, Barnes maze, tail suspension, contextual and cued fear‐conditioning tests, as previously described . Behavioral testing was performed between 9:00 am and 6:00 pm .…”
Section: Methodsmentioning
confidence: 99%
“…The mice were tested in the following order: general health and neurological screen, light/dark transition, open field, elevated plus maze, hot plate, social interaction, rotarod, three-chamber social approach, ASR/PPI, Porsolt forced swim, T-maze spontaneous alternation, Barnes maze, tail suspension, contextual and cued fear-conditioning tests, as previously described. 27 Behavioral testing was performed between 9:00 AM and 6:00 PM.…”
Section: Behavioral Test Batterymentioning
confidence: 99%
“…The percentage of alternation was calculated as (alternation/maximum alternation) × 100. Data acquisition and analysis were performed automatically using the ImageYM program …”
Section: Methodsmentioning
confidence: 99%
“…Behavioral data were obtained automatically by applications (ImageLD, ImageEP, ImageSI, ImageCSI, ImagePS, ImageYM, and ImageFZ) based on the public domain NIH Image program and ImageJ program, and modified for each test.…”
Section: Methodsmentioning
confidence: 99%